Selective release of HMG nonhistone proteins during DNase digestion of Tetrahymena chromatin at different stages of the cell cycle. - Hamana, K (1980)
The possible role of LG-1, a Tetrahymena specific HMG protein found in the macronuclear chromatin (Hamana, K. and Iwai, K. (1979) J. Biochem. 86, 789-794), was examined in relation to the chromatin structure. The chromatin isolated from cells synchronized at different stages of the cell cycle contained about one molecule of LG-1 per nucleosome. Limited digestion of the chromatin with DNase I or micrococcal nuclease selectively released LG-1 with the nucleosomal core histones and H1 remained insoluble, bound to the resistant DNA. Depending on the cell stages several types of chromatin structure were distinguished by their nuclease sensitivity. However, the chromatin at different stages exhibited the similar behavior of the LG-1 release with the nucleases as a function of the degree of chromatin solubilization. The results suggest that LG-1 proteins play a role in the chromatin organization which is rather independent of the cell stages.